IDENTIFIKASI KETERSEDIAAN AIR DAS INDRAGIRI UNTUK MEMENUHI KEBUTUHAN AIR BAKU RUMAH TANGGA DAN INDUSTRI - Nurlaili; Manyuk Fauzi; Muhammad Yusa (Racic : Rab Construction Research, 2025)
The Indragiri Watershed serves as the lifeblood for the communities surrounding it, functioning as a source of raw water for households, industry, agriculture, and as a transportation route. This study aims to identify the water availability in the Indragiri Watershed to meet the raw water needs of households and industries, in order to assess the watershed’s capacity to fulfill the water demands of its users. This research links water availability with water demand in the Indragiri Watershed. Based on the research findings, it can be concluded that water availability in the Indragiri Watershed under all seasonal scenarios is in a surplus condition. This indicates that the water availability in the Indragiri Watershed is still sufficient to meet the water demands of all its users.